On the phenotypic spectrum of serine biosynthesis defects - El-Hattab, Ayman W.; Shaheen, Ranad; Hertecant, Jozef; Galadari, Hassan I.; Albaqawi, Badi S.; Nabil, Amira; Alkuraya, Fowzan S. (Journal of inherited metabolic disease, 2016)
L-serine is a non-essential amino acid that is de novo synthesized via the enzymes phosphoglycerate dehydrogenase (PGDH), phosphoserine aminotransferase (PSAT), and phosphoserine phosphatase (PSP). Besides its role in protein synthesis, L-serine is a precursor of a number of important compounds. Serine biosynthesis defects result from deficiencies in PGDH, PSAT, or PSP and have a broad phenotypic spectrum ranging from Neu-Laxova syndrome, a lethal multiple congenital anomaly disease at the severe end to a childhood disease with intellectual disability at the mild end, with infantile growth deficiency, and severe neurological manifestations as an intermediate phenotype. In this report, we present three subjects with serine biosynthesis effects. The first was a stillbirth with Neu-Laxova syndrome and a homozygous mutation in PHGDH . The second was a neonate with growth deficiency, microcephaly, ichthyotic skin lesions, seizures, contractures, hypertonia, distinctive facial features, and a homozygous mutation in PSAT1 . The third subject was an infant with growth deficiency, microcephaly, ichthyotic skin lesions, anemia, hypertonia, distinctive facial features, low serine and glycine in plasma and CSF, and a novel homozygous mutation in PHGDH gene. Herein, we also review previous reports of serine biosynthesis defects and mutations in the PHGDH, PSAT1 , and PSPH genes, discuss the variability in the phenotypes associated with serine biosynthesis defects, and elaborate on the vital roles of serine and the potential consequences of its deficiency.